Population pharmacokinetic models of first choice beta-lactam antibiotics for severe infections treatment: What antibiotic regimen to prescribe in children? - Amélie Marsot (Frontiers Media S.A., 2020)
Background: To perform a review describing the pharmacokinetic (PK) parameters and covariates of interest of the eight first choice β-lactams (BL) antibiotics for treatment of severe infections in pediatric population. Pediatric sepsis and septic shock reportedly affect 30% of children admitted to pediatric intensive care units, with a 25% mortality rate. Eight BL are included as first choice antibiotic for severe infections in pediatric population in the World Health Organization model list of essential medicines for children. Methods: The PubMed/Medline databases was searched and included studies if they described a population PK model of piperacillin, amoxicillin, ampicillin, cefotaxime, ceftriaxone, cloxacillin, imipenem or meropenem in neonates or children. We compared the PK parameters for each drug. We analysed the used covariates to estimate PK parameters. We compared the pharmacokinetics/pharmacodynamics (PK/PD) targets and the drug dosing recommendations. Results: Thirty-four studies met inclusion criteria with seven studies for piperacillin, five for amoxicillin, three for ampicillin, three for cefotaxime, two for ceftriaxone, two for imipenem and twelve for meropenem. None met inclusion criteria for cloxacillin. Ages ranged from 0-19.1 years with 12 studies including preterm. Body weight, age and renal function were the three major covariates in neonates and children. Different PK/PD targets were observed (between 40% to 100% of the dosing regimen interval of time over which the unbound (or free) drug concentration remains above the minimal inhibitory concentration (MIC) (fT>MIC) or four times the MIC (fT>4xMIC)). Several drug-dosing regimens were fond recommended according to the age and pathogens MIC using intermittent, timed or continuous infusions. Conclusions: Consensus is lacking on the optimal dosing regimens for these eight first choice antibiotics. A more personalized approach to antibiotic drugs dosing with individual characteristics of patient and pathogen susceptibility is required. According PK/PD targets and used dosing regimens, prospective clinical studies are required to investigate clinical cure, patient survival and emergence of antimicrobial resistance.